The penguin family book - Sømme, Lauritz, 1931- (Picture Book Studio, 1988)
Text and photographs portray a colony of chinstrap penguins on Bouvet Island in the Antarctic Ocean, from spring when they lay their eggs, through summer when the chicks hatch, to autumn when they leave the island until their return next spring.